Children's Work and Schooling : Does Gender Matter? Evidence from the Peru LSMS Panel Data - Ilahi, Nadeem (World Bank, Washington, DC, 2014)
Using panel data from Peru, the author investigates the determinants of the allocation of boys' and girls' time to schooling, housework, and income-generating activities. Specifically, she explores whether sickness, female headship, access to infrastructure, and employment of women in the household have different impacts on the time use of boys and girls. Girls mostly engage in housework, and boys mostly work outside the home. As a work activity, housework responds to economic incentives and constraints. The author's econometric findings suggest that changes in household welfare affect girls' work and schooling more than boys'. Even though boys' and girls' educational attainment rates are the same, girls' education responds more to changes in household welfare than does boys'. Similarly, girls are more likely than boys to adjust their home time in response to changes in adult female employment and to sickness of household members. Lack of access to energy infrastructure lowers the educational attainment of both boys and girls but has little affect on their labor. The traditional approach to the determinants of child labor and education excludes housework and may understate children's time use, particularly that of girls. It may therefore also overlook an important gender dimension of education policy. Safety nets that protect household incomes from employment shocks and sickness, and childcare programs that allow women to work, would reduce the likelihood of girls being pulled out of school.